Hybrid Methodology Involving Scrum and Waterfall Model towards the Software Project Development in Academic Knowledge Centers - Sonali Pathak; Pallavi Saxena (Institute of Advanced Engineering and Science, 2012)
Software project development in academia has the core objective to provide the student with an effective space to work in a team, interact with users, develop prototype, develop documentation, and improve presentation skills. An academic survey was done and it was found that the major challenge being faced by the institutes is the slack in controlling and tracking the project development activities. This results in poor quality software product which is in no way comparable with the industrial projects. Also, the ineffective use of tools and technologies are of great concern. The lack of proper and effective communication among the team members as well as with their project supervisor is also a major problem. Factors like, lack of enthusiasm, commitment, and financial support invite unwarranted risks. Such unstructured and uncontrolled way of working often leads to unsuccessful projects. All these factors show that academia is lacking more on the managerial issues rather than technological issues.DOI: http://dx.doi.org/10.11591/ijere.v1i1.456